Pembiasaan Shalat Berjamaah dan Kedisiplinan Siswa di MTs Daarul Mustaqiem Bogor - Laelasari, Eda (Al-Wasathiyah: Journal of Islamic Studies, 2022)
The research, entitled Habituation of Congregational Prayer and Student Discipline at MTs Daarul Mustaqiem Pamijahan, Bogor Regency (Correlational Studies) was a survey research with an associative type of quantitative approach. The research aims to: 1) obtain data on the habit of praying in congregation at MTs Daarul Mustaqiem Pamijahan, Bogor Regency; 2) obtaining student discipline data at MTs Daarul Mustaqiem Pamijahan, Bogor Regency; 3) find out the correlation between the habit of praying in congregation with student discipline at MTs Daarul Mustaqiem Pamijahan, Bogor Regency. This research was conducted at MTs Daarul Mustaqiem Pamijahan, Bogor Regency. The total research population is 481 people. Samples were taken using a simple random sample technique as many as 30 respondents. The research approach uses quantitative methods. The technique of returning data is using a questionnaire. The research instrument used a questionnaire for the habit of praying together and student discipline. Instrument testing with validity test and reliability test. Data analysis technique, to determine the correlation of variable X (congregational prayer habit) with variable Y (student discipline) using Pearson Product Moment correlation test technique. The calculated r index is 0.649, which is greater than r table = 0.361, which is significant. This means that the habit of praying in congregation has a correlation with student discipline. The KD index (Coefficient of Determinant) was obtained 42.12% which indicates that the variable X (habitual prayer in congregation) contributes as much as 42.12% of variable Y (student discipline), and the rest is about 57.88% determined by other factors.